Study and analysis of the appearance of religion on the ground of Hegel's phenomenology - Amir Aghajanloo; ali fathi; seyyed Mohammad Taqi chawoshi (حکمت اسرا, 2021)
The phenomenology of knowledge is the experience of consciousness. Hegel showed that the realization of absolute knowledge is possible only through the dialectical method and the phenomenological perspective. Unlike Enlightenment thinkers, he considered religion an integral part of human thought. In this article, we are going to answer the question of what is the fate of religion in Hegel's phenomenological view and what is its place in the system of knowledge? The answer is that religion is one of the most important positions in which the Absolute emerges. The absolute abode and manifestation in religion is neither tangible nor purely intellectual, but an intermediate house which Hegel calls (vorstellung) or as if or representation.